2018
DOI: 10.1094/mpmi-05-17-0117-r
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific Symbiosis Between Sophora flavescens and Different Rhizobia

Abstract: We explored the genetic basis of the promiscuous symbiosis of Sophora flavescens with diverse rhizobia. To determine the impact of Nod factors (NFs) on the symbiosis of S. flavescens, nodulation-related gene mutants of representative rhizobial strains were generated. Strains with mutations in common nodulation genes (nodC, nodM, and nodE) failed to nodulate S. flavescens, indicating that the promiscuous nodulation of this plant is strictly dependent on the basic NF structure. Mutations of the NF decoration gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…Bradyrhizobiaceae were depleted in roots of soybeans inoculated with the noeI mutant. This might be explained by a reduction in compatibility between the host plant and Bradyrhizobium caused by noeI mutation [50].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bradyrhizobiaceae were depleted in roots of soybeans inoculated with the noeI mutant. This might be explained by a reduction in compatibility between the host plant and Bradyrhizobium caused by noeI mutation [50].…”
Section: Discussionmentioning
confidence: 99%
“…1a) that consisted of two rhizobial genotype treatments and two planting patterns. The rhizobial genotype treatments included: 1) B. diazoe ciens USDA 110 wild type, isolated from soybean [52]; and 2) B. diazoe ciens USDA 110 noeI mutant, obtained from our previous study [50]. The two planting patterns were 1) planted with cultivated soybean (C08) and 2) intact soil without plants (unplanted).…”
Section: Greenhouse Experiments and Symbiotic Phenotype Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study found that the growth of SFA is greatly influenced by rhizobial nodulation using different rhizobial strains and specific gene mutants (Liu et al . 2018a). Plants grow poorly (characterized by the yellow leaves and lower chlorophyll content) when they are inoculated with a rhizobium harbouring a nodC gene mutation or when they are not inoculated (Liu et al .…”
Section: Resultsmentioning
confidence: 99%
“…The nitrogen fixing ability of B. diazoefficiens USDA110 noeI mutant was degraded. Furthermore, single noeI or double nodZnoeI mutant of S. fredii CCBAU45436 showed decreasing nodule number, although their nitrogen fixing abilities were normal (Liu et al, 2017b ). Although there are no specific genes shared by the soybean microsymbionts (Tian et al, 2012 ), all above indicates that rhizobial Nod factor compositions are much conserved, and that they are more related to host range than to phylogenetic relationship.…”
Section: Discussionmentioning
confidence: 99%